Analisis Kebijakan Pengembangan Wilayah Dengan Dukungan Transportasi Antar Pulau Di Kabupaten Administratif Kepulauan Seribu - Kurniawati, Fita (Warta Penelitian Perhubungan, 2010)
Regional Government of DKI Jakarta and Kepulauan Senbu have autlwrihj to develop and manageall of the regional resources in order to gain society welfare which remains on three nzain purposes ofdevelopment. As a matter of fact, the government poli.Clj sometimes does not meet the needs of publicdemands due to the existing condition. One common problem face biJ Kepulauan Senbu is ineffectivenesspoli.Clj programs due to the condition exist and the low level aaessibilitt/ s. T7ierefore, this policyresearch tries to identifiJ and analyze the government's poli.Clj compares to the existing situation. T71eresult of study showed that there are policies incompatibilities 1uith the public needs dealing with theregional planning and mass transportation, lack of coordination among government institution, andthe needs of strategies and regulator's reformation especial.Ly seeing the archipelago regional planningfrom small islands development's points of view.